2020
DOI: 10.2355/isijinternational.isijint-2019-576
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Binary Phase Mixtures of Magnesium-Aluminate Spinel and Calcium-Aluminates Using Time-Gated Raman Spectroscopy

Abstract: The modification of MgO•Al 2 O 3 spinel inclusions into less detrimental mixture phases of CaO-MgO-Al 2 O 3 plays an essential role in refining calcium-treated aluminium killed steels. This study uses Raman spectroscopy for the characterisation of binary phase samples that contain MgO•Al 2 O 3 spinel and calcium aluminate (CaO) x -(Al 2 O 3 ) y phases. Samples were synthesised from MgO•Al 2 O 3 spinel (MA), Al 2 O 3 and calcium aluminate phases to achieve binary samples of CA-MA, C3A-MA, C12A7-MA and Al 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Additionally, phases such as Al 2 O 3 , MgO•Al 2 O 3 , C12A7, CA, C3A, and CaS have been measured and demonstrated to be Raman active [11][12][13][14][15]. Furthermore, Raman spectroscopy is found to be applicable in various research fields for quantitative and qualitative analysis [16], including some studies already done on synthetic [17,18] and actual [19] inclusion phase studies. However, spectroscopic techniques like Raman spectroscopy have not been used in detail to study duplex oxide-sulphide inclusions like C12A7-CaS, C3A-CaS, and CA-CaS.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, phases such as Al 2 O 3 , MgO•Al 2 O 3 , C12A7, CA, C3A, and CaS have been measured and demonstrated to be Raman active [11][12][13][14][15]. Furthermore, Raman spectroscopy is found to be applicable in various research fields for quantitative and qualitative analysis [16], including some studies already done on synthetic [17,18] and actual [19] inclusion phase studies. However, spectroscopic techniques like Raman spectroscopy have not been used in detail to study duplex oxide-sulphide inclusions like C12A7-CaS, C3A-CaS, and CA-CaS.…”
Section: Introductionmentioning
confidence: 93%
“…where I k is the intensity for the Raman shift k, x c is the calibration feature candidate, and In represents the intensity corresponding to the Raman shift n. The use of relative intensities treats the signal similarly as does the unit normalization, and thus additional normalization was not carried out. The average mean absolute error (MAE) was calculated using 4N repetitions for the cross-validation and a detailed description of how the calibration model identification and the selection process were conducted can be found in [18]. These two analytical techniques were considered in this study as complementary methods, where XRD provided information concerning individual phase weight percentage in the sample, and XRF for estimating the elemental composition of the prepared samples [28].…”
Section: Calibration Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the prospective application of Raman characterizing oxide mixtures from Al 2 O 3 , MgO•Al 2 O 3 spinel (MA), and calcium aluminates from synthetic inclusions phase [10]. In addition, the study conducted by S. Li and Hihara (2017) [11] has shown that individual phases of calcium-aluminate-based inclusions, such as CaO•Al 2 O 3 (CA), in steel samples could be identified in steel samples using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Jing et al [21] have shown that the route of inclusion modification and also the calcium content in the steel melt might affect the final inclusion composition. However, previous studies concerning the application of Raman spectroscopy for synthetic, [14,17,19,23] or steel samples [20] and nonmetallic inclusion studies have been limited to characterizing only the binary system between (CaO-Al 2 O 3 ) and the (CaS, Al 2 O 3 or MgAl 2 O 4 ) or MgO-CaO-Al 2 O 3 systems. Consequently, further studies regarding the use of Raman spectroscopy for characterizing a mixture of phases found in CaO-Al 2 O 3 -CaS and CaO-Al 2 O 3 -MgO-CaS systems will contribute to expanding the potential use of this technique for nonmetallic inclusions analysis.…”
Section: Introductionmentioning
confidence: 99%